A critical reflection on the production of this deadly air we breathe (2023) and the use of participatory and expository modes of representation in documentary films with lessons from Unearthed (2014) - Mohane, Patrick (Centre for Film and Media Studies, 2025)
Self-reflection is a critical component of both the creative and research related processes. In addition to learning through the practical process, there could also be learning about, and from the undertaken practical process itself as part of inquiry. This study accompanies the research documentary film that I have produced titled, this deadly air we breathe (2023). The analysis attempts to deliberate and answer the question of the importance and the role of the documentary modes of representation towards the realisation of any envisaged documentary film. I am analysing the use of these modes of representation against filmmaking pre-production and post-production activities such as the creation of a story outline,scripting and editing respectively. Furthermore, related to this is the filming approach and amendments thereof, that are influenced by location, space, and time. Thus, bearing in mind the changes that may occur and their implication on the final film outcomes, including future practice development and improvement for myself. The goal being to consider the learning outcomes from the process, and to reflect on how activities were undertaken, or perhaps, ought to have been undertaken in the development of my short documentary film. This study contemplates the lessons incorporated at the initial film development stages, sourced through the reference feature length documentary film Unearthed (Minnaar, 2014). Impact filmmaking is relayed as part of the resulted learning considerations added with the analysis of this deadly air we breathe film development from a film creation perspective. With the focus on context of film production from a mode perspective, a self-questioning on mode application and timing of their incorporation is also discussed. By exploring the filmmaker's testimony about the self-reflection elements, the study discerns the prospect of impact filmmaking through the lessons implied. By way of conclusion, this explication makes concession through the identification of existing impact film components, possible future opportunities for this deadly air we breathe film along those lines, and within the body of climate and environmental films.